Analysis of Demographic Trends and Human Resources in the Agrarian Sector - Steliana RODINO; Carmen Adriana GHEORGHE; Ancuta MARIN (Revista de Management Comparat International)
Agriculture is an important sector for regional economies across Europe, especially in rural areas where it supports livelihoods and ensures food security. However, its sustainability is correlated to demographic dynamics. This article explores the relationship between demographic trends and the development of agrarian sector, emphasizing the critical importance of human resources for achieving sustainable economic development. The rural and urban-rural population structure is reflecting an imbalance accentuated by demographic trends such as population aging and rural-urban migration, phenomena that reduce the availability of young labour in the agricultural sector. The comparative analysis of European regions highlighted significant variations in the demographic structure. The article highlights the importance of adopting an integrated perspective, addressing both demographic challenges and the needs to modernize the agricultural sector, to ensure the resilience of regional economies in Europe.